Medio centenar de números de la revista Espiral - Alonso Carlos, Jorge; Carvajal Barba, Raquel; Moreno, María Guadalupe; Preciado González, Jaime; Tamayo, Jaime (Espiral estudios sobre Estado y sociedad, 2015)
SIN RESUMEN